Clinical profile and management outcome of Parathyroid Adenoma - A 7 years retrospective study (Bangladesh Journal of Otorhinolaryngology, 2015)
The study aims to present the clinical profile and management outcomes of parathyroid adenoma patients in our institutions. This retrospective study included ten patients with parathyroid adenoma presented to Department of Otolaryngology and Head-Neck Surgery at Dhaka Medical College Hospital and Ibn Sina Medical College Hospital, Dhaka from January 2004 to January 2011.Out of 10 patients, 8 were female. Average age of presentation was 50 years. 6 patients were symptomatic and 4 were asymptomatic. In 8 patients, serum creatinine level was within normal limits and 2 patients had elevated serum creatinine level. All 10 patients had hypercalcaemia and increase parathormone level, from mild to severe. CT guided fine needle aspiration cytology diagnosed 2 cases preoperatively. 6 patients diagnosed with 99mTc Sestamibi scan and 3 patients diagnosed by single photon emission computed tomography (SPECTCT) dual isotope (I-123/99mTc-MIBI) substraction for imaging parathyroid adenoma. All the patients underwent parathyroidectomy except for 1 patient in whom hemithyroidectomy was done. Postoperative period was not without complications but has been managed with strong monitoring. Long term follow up was done up to 1 year with 100% cure rate. DOI: http://dx.doi.org/10.3329/bjo.v20i1.22014 Bangladesh J Otorhinolaryngol; April 2014; 20(1): 27-34